The positive repercussions of the Corona pandemic on Jordanian society - Heasat , Nadia; AL-Share , Zubaida (Dirasat: Human and Social Sciences, 2024)
Objects: This study aimed to identify the positive repercussions of the Corona pandemic in terms of economic, social and health terms. The goal is to identify the positive repercussions of the Corona pandemic on Jordanian society, and is there a relationship between the positive repercussions of the Corona pandemic and the variables that pertain to the sample members (age, gender and status). Methods: The descriptive analytical approach was used using the electronic questionnaire, where the results were as follows Most of the jobs (professionals and self-employment, private sector employees, and public sector employees) are male and female. Results: There are positive effects for the health field in the: first place in terms of public interest, sterilization, adherence to public safety measures, taking vaccinations and precautionary measures to prevent diseases and The positive social effects of the pandemic came as And Rona came in the second place, represented in the increase in social solidarity in society and the increase in family bonding between fathers and their children, and the ability of fathers and mothers to spend more time with their fathers and to identify their needs and a decline in some of the repetitive behaviors of individuals on occasions such as kissing came in third place the positive effects in The economic field, such as the reduction in cost expenditures in marriage, the spread of household production projects and their marketing, the increase in electronic sales and the acceptance of individuals to buy basic commodities and the distance from ostentatious goods, and the presence of statistically significant differences in the social dimension of the gender variable in favor of males, Conclusions: The Corona pandemic had positive effects in the economic, social and health aspects